Scaling laws of nitrogen soft X-ray yields from 1 to 200 kJ plasma focus - Akel, M. (Springer US, 2013)
Numerical experiments are carried out sys- tematically to determine the nitrogen soft X-ray yield for optimized nitrogen plasma focus with storage energy E 0 from 1 to 200 kJ. Scaling laws on nitrogen soft X-ray yield, in terms of storage energies E 0 , peak discharge current I peak and focus pinch current I pinch were found. It was found that the nitrogen X-ray yields scales on average with Y sxr;N 1⁄4 1:93 Â E 1:21 0 J (E 0 in kJ) with the scaling showing gradual deterioration as E 0 rises over the range. A more robust scaling is Y sxr 1⁄4 8 Â 10 À8 I 3:38 pinch . The optimum nitrogen soft X-ray yield emitted from plasma focus is found to be about 1 kJ for storage energy of 200 kJ. This indicates that nitrogen plasma focus is a good water-window soft X-ray source when properly designed.